A Sociolinguistic Study Of The Variety Of Ngkalongan Dialect Javanese Spoken By Pekalongan People - Silvia Nanda Putri Erito (JELLE : Journal Of English Literature, Linguistics, and Education, 2021)
Dialect is a kind of language style that happened in some nations of the country especially in Indonesia. One of the varieties of dialect is Ngkalongan dialect which is characterized by variations in pronunciation, grammatical, and discourse features. The objective of this study is to explain the dialect found in the video that will be analyzed by qualitative research design. The data is taken from the video youtube channel. The data collection method by video observation. The researcher used an instrument observation checklist and taking notes to analyze the data. The result showed that there are 20 dialect that used by the speakers in speaking ngkalongan dialect. The researcher suggests for other researchers who will conduct research dealing with another dialect in Indonesia. Keywords: Dialect, Ngkalongan Dialect, Pekalongan Javanese spoken